2011
DOI: 10.1002/nau.21120
|View full text |Cite
|
Sign up to set email alerts
|

Sophisticated models and methods for studying neurogenic bladder dysfunction

Abstract: AimTo describe how the use of new and established animal models and methods can generate vital and far reaching experimental data in the study of mechanism underlying neurogenic bladder overactivity.MethodsBladder and colonic irradiated mice and those with upper and lower motor neuron lesions were used to study neurogenic bladder overactivity. Methods included cystometry, tension measurements, afferent nerve recordings and optical mapping of action potentials and intracellular Ca2+ transients. Recordings were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Most studies have used this animal model of SCI to examine spinal cord regeneration and functional recovery (reviewed in references 6 and 7). A number of groups have investigated the neurogenic bladder phenotype in SCI rats and have demonstrated that the urodynamic profiles in these animals are similar to those seen in humans with SCI or spinal dysraphism (8)(9)(10). This suggests that the SCI rat may be a useful system for modeling UTI with neurogenic bladder.…”
mentioning
confidence: 97%
“…Most studies have used this animal model of SCI to examine spinal cord regeneration and functional recovery (reviewed in references 6 and 7). A number of groups have investigated the neurogenic bladder phenotype in SCI rats and have demonstrated that the urodynamic profiles in these animals are similar to those seen in humans with SCI or spinal dysraphism (8)(9)(10). This suggests that the SCI rat may be a useful system for modeling UTI with neurogenic bladder.…”
mentioning
confidence: 97%
“…Under such a condition, animal models seem to lend particular significance to the task (BieringSorensen et al, 2009;Krogh et al, 2009;Kanai et al, 2011). Till now, scholars have not reached an agreement on whether bladder dysfunction is caused by neurogenic or myogenic factors.…”
Section: Discussionmentioning
confidence: 99%
“…18 Imaging of Ca 2+ signaling across the bladder wall suggests that this activity may be initiated by Ca 2+ transients that originate in the mucosa. 19 Spontaneous contractions are enhanced by the mucosa, particularly if hypertrophied, for example in animals with neurogenic overactivity. 20 An unresolved issue is the nature of communication between mucosa and detrusor, this may be due to diffusion of contractile agonists or via cell-to-cell contacts.…”
Section: Introductionmentioning
confidence: 99%